PENGARUH KONSENTRASI PENAMBAHAN SODIUM NITRAT DAN SODIUM FOSFAT PADA MEDIA GUILLARD TERHADAP KONSENTRASI BIOMASSA MIKROALGA Nannochloropsis sp. - Gede Brahmantara, Ida Bagus; Anggreni, A. A. Made Dewi; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 4 (2015): Desember, 2015)
The aim of this study was to understand the effect of sodium nitrate and sodium phosphate concentration on Guillard medium to yields of biomass, and also to determine the best concentration of sodium nitrate and sodium phosphate to produce the highest yields of biomass on marine microalgae Nannochloropsis sp. Determining the effects of sodium nitrate and sodium phosphate on biomass was performed using Response Surface Methodology (RSM). The concentrations of sodium nitrate and sodium phosphate on Guillard medium affects the yields of biomass on marine microalgae Nannochloropsis sp. The optimum concentration of sodium nitrate and sodium phosphate to produce the highest yields of biomass were 178.14 g/l and 13.34 g/l respectively, with biomass concentration of 8.00 x 10 7 cell/ml. Keywords: Guillard, Nannochloropsis sp., sodium nitrate, sodium phosphate
Keywords: 74